Kaitan Gender dan Struktur Keluarga dengan Pemberian Intervensi Gizi Spesifik pada Anak Usia 6-23 Bulan - Hutagaol, Rutmauli; Pratiwi, Niken; Fratama, Ferry Fadli; Fauziah, Erna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to explore the relationship between gender and family structure by providing specific nutritional interventions to children aged 6-23 months. The method used was analytical observational with a cross-sectional approach. The research results from chi-square analysis showed that there was a significant relationship between the child's gender and family type and the provision of specific nutrition (p value <0.05). The majority of male children received positive specific nutrition, namely 52.2%, and girls received positive specific nutrition, namely 64.9%. The nuclear family type provided specific nutrition positively by 63.1% and the large family type provided specific nutrition negatively by 52.8%. In conclusion, the child's gender and family type have a significant influence on the provision of specific nutrition and nuclear families are more likely to provide better nutrition. Keyword: Child's Gender, Provision of Specific Nutrition, Stunting, Family Type